Clinico–Pathological Features of Diffuse Midline Glioma, H3 K27-Altered in Adults: A Comprehensive Review of the Literature with an Additional Single-Institution Case Series - Giuseppe Broggi; Serena Salzano; Maria Failla; Giuseppe Maria Vincenzo Barbagallo; Francesco Certo; Magda Zanelli; Andrea Palicelli; Maurizio Zizzo; Nektarios Koufopoulos; Gaetano Magro; Rosario Caltabiano (Diagnostics)
Background: Diffuse midline glioma (DMG), H3 K27-altered, is a WHO grade 4 malignant glioma located at midline structures, including the thalamus, brainstem and spinal cord. While H3 K27-altered DMG is more common in pediatric age in which it shows a uniformly aggressive clinical behavior, its occurrence is relatively unusual among adults, and its clinico–pathological and prognostic features are not fully characterized in this age group. Methods: In this present paper, a review of the literature, including all cases of adult H3 K27-altered DMG published from January 2010 to December 2023 was performed, and the following clinical parameters were evaluated: sex, age (median and range), anatomic site, median follow-up, leptomeningeal dissemination, local recurrence and treatment. In addition, the clinico–pathological features of three additional adult cases from our retrospective series were also reported and discussed. Results: All tumors from our series exhibited a high-grade morphology with brisk mitotic activity; microvascular proliferation and necrosis were seen only in one case. The immunohistochemical loss of H3 K27me3 along with diffuse and strong immunoreactivity for H3 K27M was found in all cases, leading to the diagnosis of H3 K27-altered DMG. Conclusions: The literature review showed that adult H3 K27-altered DMG more frequently occurred in males aged between 18 and 40 years. The thalamus was the most affected site, followed by the brainstem and spinal cord, in both sex groups. Adult tumors exhibited less aggressive clinical behavior, with leptomeningeal dissemination and local recurrence reported in only 23.78% and 37.75% of cases, respectively.